2023
DOI: 10.3390/agriculture13020262
|View full text |Cite
|
Sign up to set email alerts
|

Identification of QTL Associated with Agro-Morphological and Phosphorus Content Traits in Finger Millet under Differential Phosphorus Supply via Linkage Mapping

Abstract: Finger millet (Eleusine coracana (L.) Gaertn.) is one of the most important cereal crops for people in Asia and Africa. It supplies energy and nutrients for all people, particularly poor people in these continents. Phosphorus (P) is an essential macronutrient for plant growth and grain quality, so an adequate amount of P is required for healthy plant life. There is considerable evidence that P deficiency affects the growths and yields of all cereals, including finger millet. The present study aimed at identify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 111 publications
0
5
0
Order By: Relevance
“…A total of 55 QTLs, associated with agro-morphological and P-content traits, were detected in finger millet under low P condition (Maharajan et al, 2023). Similarly, Gao et al (2020) identified several QTL for PUE and P acquisition efficiency and yield-related traits at the maturity stages in 128 RILs of barley under low P conditions (Gao et al, 2020).…”
Section: 1mentioning
confidence: 91%
See 1 more Smart Citation
“…A total of 55 QTLs, associated with agro-morphological and P-content traits, were detected in finger millet under low P condition (Maharajan et al, 2023). Similarly, Gao et al (2020) identified several QTL for PUE and P acquisition efficiency and yield-related traits at the maturity stages in 128 RILs of barley under low P conditions (Gao et al, 2020).…”
Section: 1mentioning
confidence: 91%
“…A total of 55 QTLs, associated with agro‐morphological and P‐content traits, were detected in finger millet under low P condition (Maharajan et al., 2023). Similarly, Gao et al.…”
Section: Genetic Strategies For Increasing the Uptake Of Minerals Und...mentioning
confidence: 99%
“…Compared to other major cereals, QTL associated with improving nutrients' use and acquisition efficiencies have not been identified much in millets. Recently, more than 50 QTL associated with various agro-morphological, phosphorus contents in shoot and roots and biomass traits were identified in 100 RILs of finger millet using 101 SSR markers under low-and high-phosphate conditions [68]. The same group also identified eight QTL for root-and shoot-related traits under the same low-and high-phosphate conditions using 87 SSR markers in finger millet through association mapping [69].…”
Section: Qtl Associated With Various Traits In Major and Minor Milletsmentioning
confidence: 99%
“…Studies at the University of Georgia have characterized a bi‐parental interspecific population (MD‐20 × Okhale 1) (Qi et al, 2018) to map for days to flowering, plant height, panicle number per plant and blast disease resistance (Pendergast et al, 2022), and colouration of stigma and anthers (Devos et al, 2023). A mapping population between IE‐2606 and PR‐202 consisting of 100 individuals was characterized for agro‐morphological traits and protein content, identifying several QTLs (Maharajan et al, 2023). Table 8 summarizes MTAs conducted in finger millet that used at least 100 genotypes and a minimum of 100 markers in the trait characterization.…”
Section: Genetic and Genomic Resources Of Finger Milletmentioning
confidence: 99%